Phenylalanine requirements of enterally fed term and preterm neonates. Issue 6 (29th April 2015) - Hogewind-Schoonenboom, Jacomine E; Zhu, Li; Zhu, Lin; Ackermans, Eveline CAM; Mulders, Renske; te Boekhorst, Bart; Wijnen, Mandy; Bijnevelt, Lianne; Voortman, Gardi J; Schierbeek, Henk; Huang, Lisha; de Groof, Femke; et al.
ABSTRACT: Background: Phenylalanine, which is an essential aromatic amino acid, is either used for protein synthesis or irreversibly hydroxylated to tyrosine. The provision of optimal amounts of dietary phenylalanine is not only important for growth and development but might also influence catecholamine synthesis and release rates. The current recommended aromatic amino acid requirement for infants aged 0–6 mo is based on the amino acid content of human milk. Objective: We quantified the requirements for phenylalanine in the presence of excess tyrosine (166 or 177 mg/kg per day for term and preterm infants, respectively) for term and preterm neonates by using the indicator amino acid oxidation method with l -[1- 13 C]lysine 2HCl as an indicator. Hence, we determined the minimum obligatory phenylalanine requirement. Design: Fully enterally fed term and preterm infants received randomly graded amounts of phenylalanine (5–177 mg/kg per day) as part of an elemental formula. Data are expressed as means ± SDs. Results: Twenty term (birth weight: 3.19 ± 0.34 kg; gestational age: 38.9 ± 1 wk) and 16 preterm (birth weight: 1.75 ± 0.17 kg; gestational age: 32.5 ± 0.6 wk) Asian infants participated at a postnatal age of 17 ± 8 d. In total, 44 studies were performed. The minimum obligatory phenylalanine requirement was 58 mg/kg per day (95% CI: 38–78 mg/kg per day) and 80 mg/kg per day (95% CI: 40–119 mg/kg per day) for term and preterm infants, respectively. Conclusion: The determined mean phenylalanine-requirement estimates are lower than the contents of term and preterm formulas currently on the market. This trial was registered at www.trialregister.nl as NTR1610.